Выбор материала анода при электролизе растворов сульфатов с деполяризацией SO₂ - Байрачный, Борис Иванович; Тульская, Алена Геннадьевна; Сенкевич, А. В.; Желавский, С. Г. (НТУ "ХПИ", 2014)
Исследован процесс электролиза сульфатных растворов с деполяризацией SO₂ с использованием платиновых анодов и анодов из стеклографита. Показана перспективность использования пористых графитовых анодов с каталитически активными покрытиями платиной, оксидами вольфрама и молибдена.

Theoretical mechanism of anodic depolarization process in Hybrid sulfur cycle for producing hydrogen was substantiated. Diagram of the dependence of sulfur-containing particles on the pH of the electrolyte solution was and designed buil. Practical research agreed with the calculated data and confirm the nature of the anodic process associated with the oxidation of SO₂ on platinum anode.
Choosing of material in electrolysis of sulphate solutions with SO₂ depolarization
Keywords: платина; стеклографит; depolarization; sulfur dioxide; platinum anode